The Effect of the Amount of Stevia Leaf Powder (Stevia rebaudiana) and Drying Time on the Quality of Snake Fruit Padang Sidempuan Dried Candied - Armaya, Riska Putri; Lubis, Linda Masniary; Nurminah, Mimi (Talenta Publisher, 2024)
This study aimed to determine the Effect of using stevia leaves as a natural sweetener on dried sweets of Padang Sidempuan's snake fruit. The method used in this study was the factorial Complete Randomized Design (CRD) method with two factors, namely the amount of stevia leaf powder (0,20%: 0,25%; 0,30%; 0,35%) and drying time (4, 6, 8 and 10 hours). The tests carried out were moisture content, ash content, total sugar, total dissolved solids, total microbes, acidity (pH), and organoleptic tests of colour, flavour, taste, and texture. This study's results showed a highly significant effect exerted by the amount of stevia leaf powder on moisture content, ash content, total dissolved solids, total sugar, total microbes, acidity (pH), and an organoleptic test of colour, flavour, and taste. Drying time significantly affected moisture content, ash content, total sugar, total microbes, total dissolved solids, and texture organoleptic test. The interaction between the amount of stevia leaf powder and the drying time had a highly significant effect on moisture content and a significantly different effect on total microbes and organoleptic colour. The amount of stevia leaf powder is 0,35%, and the drying time of 8 hours results in the best treatment on dried sweets of Padang Sidempuan's snake fruit.